2004
DOI: 10.1021/ma0494030
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched Blue-Light-Emitting Alternating Copolymers of Tetrabromoarylmethane/Silane and 9,9-Dihexylfluorene-2,7-diboronic Acid

Abstract: The first soluble hyperbranched tetrahedral polymers were prepared by Suzuki coupling polycondensation reaction between tetrabromoarylmethane/silane and 9,9-dihexylfluorene-2,7-diboronic acid at low concentrations. The polymers exhibited high thermal stability with their decomposition temperatures (T ds) in the range 352−449 °C. The polymers emitted blue light highly efficiently in both solution and the solid state. The photoluminescence quantum efficiencies of the polymers in THF solution were in the range 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 46 publications
0
46
0
Order By: Relevance
“…To conclude, from the results it is demonstrated that the given molecular constructions are distinguished by a high degree of tetrahedral shape persistency, providing impact as structurally controlled subunits for the future design of supramolecular building blocks such as precursors of dendrimers [41], polymers [20,42], liquid crystals [43] or materials with other applications [21].…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, from the results it is demonstrated that the given molecular constructions are distinguished by a high degree of tetrahedral shape persistency, providing impact as structurally controlled subunits for the future design of supramolecular building blocks such as precursors of dendrimers [41], polymers [20,42], liquid crystals [43] or materials with other applications [21].…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Recently, a series of tetraphenylsilane-based hyperbranched blue-light-emitting alkylfluorene copolymers were developed by He and coworkers. [17][18][19] No excimer formation in longer wavelength like emissions at 500-600 nm was observed for such hyperbranched PFs. The color purity of blue emissions was shown to be improved by the reduction of the aggregates formed by polymer-chain p-p stacking in the solid state of PFs.…”
Section: Introductionmentioning
confidence: 89%
“…However, the presence of the tetrahedral molecular skeleton of tetraphenylsilane groups or the hyperbranched structure effect on the reduced aggregation and excimer formation of PF were not clarified. [17][18][19] More recently, a comparative study on light-emitting copolymers of fluorene and carbazole with a full conjugated or Si-interrupted structure was carried out by He et al 20 The results seem to conclude that the self-aggregation of PF could be significantly reduced because of the steric effect of the tetrahedral molecular skeleton of teterphenylsilane groups. In fact, the maximum and full width at half-maximum (fwhm) of the emissions were not reduced as the conjugated structure was interrupted by the teterphenylsilane group.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperbranched polymers (HPs) are highly branched polymers prepared from multi‐functional monomers. In addition to their easy synthesis , their three‐dimensional dendritic structure confers them with many advantageous properties over traditional linear polymers such as their non‐aggregation, high solubility , and low viscosity. Considerable research attention has been devoted to hyperbranched polymers in recent years owing to their interesting properties, which makes them potential candidates for applications ranging from coatings , non‐linear optical materials , light‐emitting diodes and sensors to catalysis .…”
Section: Introductionmentioning
confidence: 99%